Cartographic knowledge, colonialized-colonizer spaces: Egyptian maps of Harar, 1875–1885. (July 2022) - Ben-Dror, Avishai
Abstract: This paper introduces a break with the traditional monolithic view of colonial cartography in Africa, in which cartography as a colonial instrument belonged only to the European powers. These took credit for cartographical projects, without acknowledging the work of non-European powers. It historically contextualizes the Egyptian cartography of Harar (today in Ethiopia) during 1875–1885, and throws light on various aspects such as European and Egyptian production and reproduction of cartographic knowledge, cartography's role in the establishment of an Egyptian colonial core in Harar, and its representations of a non-European urban colonial hub, as well as a symbols of territoriality and sovereignty. The paper also reveals the later British and Ethiopian reproduction of Egyptian cartographic knowledge, which practically served their own imperial interests in Harar's region since mid 1880s, and illuminates the significance of the Egyptian cartographic knowledge to shaping of twentieth century's Egyptian historical narratives and collective memories. Highlights: Maps are crucial for understanding the history of Harar and the Gulf of Aden. Egyptian maps represent 1875–1885's urban and rural Egyptian colonial spaces. Maps illuminate connections between knowledge and power, territoriality and sovereignty. Egyptian maps as an integral part of the African colonial knowledge. Cartography forms connections between national identities and communities of memory.